Androgen Receptor Expression Is a Predictor of Poor Outcome in Urothelial Carcinoma - Szabados, Bernadett; Duncan, Sarah; Choy, Julia; Jackson-Spence, Francesca; Toms, Charlotte; Trevisan, Giorgia; Berney, Daniel M.; Powles, Thomas; Ackerman, Charlotte (Frontiers in Urology, 2022)
BACKGROUND: Several preclinical and clinical studies demonstrated strong correlation between androgen receptor (AR) signaling and bladder tumorigenesis. This study aims to evaluate the prognostic significance of AR expression in metastatic urothelial carcinoma (mUC). METHODS: Samples from a phase III trial (NCT00949455) which compared maintenance lapatinib versus placebo after completion of first-line, platinum-based chemotherapy in patients with HER 1/2–positive mUC of the bladder were collected. Corresponding baseline and follow-up data included patients enrolled onto study and those who screen failed. AR expression was assessed, by a single pathologist, independently and blinded. Samples were grouped according to AR expression (negative vs positive) and correlated with baseline tumor characteristics and survival. RESULTS: Of the 446 screened samples in the LAMB study, 90 were retrospectively analyzed for AR expression. There were no correlations between AR expression and tumor stage (r= -0.10), tumor grade (r= 0.05) at diagnosis or subsequent treatment with lapatinib (r= -0.04). The median progression-free survival was 6 months (95%CI, 3.20-6.80) in the AR negative group and 5 months (95%CI, 3.41-6.59) in the AR positive group [HR 0.54 (95% CI, 0.31-0.92); p=0.02]. Similarly, patients with AR negative disease had more favorable overall survival (OS) with 16 months (95% CI, 6.6 to 25.4) and 11 months (95% CI, 7.0-15.0) in the AR positive group [HR 0.55 (95% CI, 0.31-0.98); p=0.04]. In the multivariate analysis, AR expression was significantly associated with worse OS (p=0.045). CONCLUSIONS: AR expression is a predictor of poor outcome and presents a targetable alteration in patients with mUC.